Promising Natural Products in Crop Protection and Food Preservation: Basis, Advances, and Future Prospects - Temitope A. Ogunnupebi; Abimbola P. Oluyori; Adewumi O. Dada; Oluwole S. Oladeji; Adejumoke A. Inyinbor; Godshelp O. Egharevba (International Journal of Agronomy)
The increase in demand for agricultural produce necessitates the continuous search for affordable, ecofriendly, readily available crop protectors, and food preservatives. Historically, the use of various chemicals was employed in controlling plant diseases and to maintain food quality. In the past few decades, several natural product-based alternatives have been discovered and projected as better alternatives to synthetic pesticides and other synthetic agrochemicals. Recent studies focusing on the application of different botanicals in crop protection and food preservation were carefully selected and reviewed. The application of plant extract in the biogenic preparation of nanoparticles was also reviewed. This review confirms that several natural products can be used as a safe replacement for synthetic agrochemicals. Different plant extracts have also served as feed for the synthesis of nanoparticle, which is increasingly applicable in crop protection and food preservation.